Exploring the formation of treatment program director perceptions on entry-level social workers' substance use treatment capacities in New York. Issue 4 (2nd October 2021) - Minnick, Dane; Park, Daejun
Abstract: Background: This article examines how program directors of substance use treatment providers in New York state form their perceptions on the overall substance use treatment service delivery capacities of newly graduated, entry-level social workers. Methods: The study discussed consisted of a cross-sectional, quantitative survey of treatment program directors in New York state ( n = 245). Program directors were asked to rate entry-level social workers' treatment skills, knowledge of treatment concepts, and overall preparedness to deliver treatment services in the field upon first entering the professional workforce. The collected data were then analyzed using multiple regression analyses to identify associations between the skill and knowledge items and perceptions of overall preparedness. Results: The results of the study showed that five of the ten skill and knowledge competency items were significantly linked with program directors' perceptions of entry-level social workers' overall preparedness to deliver treatment services, with the model accounting for 62% of the variance in the dependent variable. Of the independent variables with significant associations, the assessment competency item accounted for 50% of the variance, while the other four variables explained 1.2–6.4% of the variance respectively. Conclusions: The findings of the study suggest that training curriculums should strongly emphasize assessment competencies for new practitioners, and that implementing a standardized training curriculum is beneficial for the professional growth and preparedness of practitioners entering into the treatment field.